Mismatch in the housing supply for most of the population - Mustapa, Nor Atiqah; Raji, Fauziah (2017)
Purpose - This paper provides an overview of the housing supply in Malaysia and specifically in Johor.One of the obvious problems in the housing market is the existence of unsold and overhang problem.The houses offered might not have matched the buyers’ housing preferences, or in simple words, there was a mismatch between the available housing and populations’ housing demand.The mismatch may be caused by the house price aspects since the house price is closely related to the buyers’ financial capability.In response to this issue, the objective of this paper is to explore the overhang units and housing supply in terms of price and at the same time get insight the developer preferences in supplying houses.Methodology - The data from the Property Market Report has been compiled and presented in this paper.The data regarding overhang units in Malaysia and Johor Bharu were analysed in terms of the house price. Furthermore, this paper also examines the housing newly launched in terms of price and the median house price movement in Johor Bahru to capture the evidence from the housing market. Next, in order to strengthen the evidence from the market report, a qualitative research approach was also employed for this paper.Therefore, semi- structured interviews were conducted with several developers in order to obtain their preferences in housing supply. Findings - By using data from Property Market Report issued by the Valuation and Services Department, it can be seen that there are overhang housing units reported each year.It was found that most of the overhang units were beyond the financial ability of the vast majority of the Malaysian population given the fact that most of them categorized under the lower income (B40) and middle income (M40), about 40% respectively (Budget 2016). The same situation happens in Johor, most of the overhang units are unaffordable to the majority population. In the case of Johor Bahru district, the trend of house price of new supply keep increasing from year to year and consequences, most of the housing in the market including the current supply is found expensive and unaffordable. Through interviews with several developers in Johor Bahru, it was found that the developer prefers to build house priced at RM500, 000 and above. Clearly, the developer targets the high income and Singaporean purchaser.They were not keen on building affordable housing even though the demand is high.This situation contributes to the overhang supply as the majority population did not have financial ability to purchase them. A mismatch exists between the population’s housing demand and housing supply in terms of price.